2023
DOI: 10.1021/acsomega.2c07708
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Drug Targets: Disordered Proteins in the Drug-Discovery Realm

Abstract: Intrinsically disordered proteins (IDPs) and regions (IDRs) form a large part of the eukaryotic proteome. Contrary to the structure−function paradigm, the disordered proteins perform a myriad of functions in vivo. Consequently, they are involved in various disease pathways and are plausible drug targets. Unlike folded proteins, that have a defined structure and well carved out drug-binding pockets that can guide lead molecule selection, the disordered proteins require alternative drug-development methodologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 230 publications
0
10
0
Order By: Relevance
“…Secondly, it suggests that iterative analog optimization is a feasible strategy to generate high-affinity ligands of disordered proteins, following similar paradigms well-established for structured protein targets. 41…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it suggests that iterative analog optimization is a feasible strategy to generate high-affinity ligands of disordered proteins, following similar paradigms well-established for structured protein targets. 41…”
Section: Discussionmentioning
confidence: 99%
“…1. Such exploitation of a disorder-to-order transition of an intrinsically disordered protein (IDP) or region (IDR) is of therapeutic interest, [36][37][38] especially when induced by a native binding partner; for example, p27 with Cdk2/cyclin A, 39,40 MAX with cMyc, 41,42 and p53 with MDM2. [43][44][45] Thus, the approach we describe herein for Rpn10:E6AP, whereby binding is monitored by using environmentally sensitive uorophores as sensors for conformational switching, can be applied generally to other therapeutically relevant protein systems to either characterize dynamic behavior and/or to perform high-throughput (HTP) screening for therapeutic discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Such conformations often lack a stable and single active binding site that can be used for in-silico screening and designing small molecules. Despite these obstacles, targeting PDPs is a critical area of research due to their significant role in various biological processes 6 and their link to a multitude of human diseases, such as cancer 2 , neurodegenerative diseases 3 and many others 6 . Previous analyses of the structures of 51 intrinsically disordered proteins (IDPs), which are PDPs that have no stable secondary structure fold at all, revealed that on average, PDPs contain 50% more druggable pockets than fully structured proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The process of discovering new drugs is both expensive and time-consuming, facing several hurdles including the challenge of finding at the preclinical level effective drug candidates through high-throughput screening methods, which often have low success rates 1,2 . To tackle these issues, the use of computer-aided drug discovery (CADD) has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%